Bio-based copolyesters poly(butylene 2, 6-naphthalate-co-butylene furandicarboxylate) derived from 2, 5-furandicarboxylic acid (FDCA): Synthesis, characterization, and properties. (November 2020) - Wang, Guoqiang; Yu, Jiayi; Jiang, Min; Wang, Rui; Liang, Yin; Zhou, Guangyuan
Abstract: A series of copolymers poly(butylene 2, 6-naphthalate-co-butylene furandicarboxylate) (PBNFs) derived from 2, 5-furandicarboxylic acid (FDCA) were synthesized. The molecular weight, microstructures, thermal and mechanical properties were characterized. DSC results show that PBN and PBNF25 can crystallize rapidly. However, the crystallization rates of PBNF50, PBNF75 and PBF are very slow. The T d, 5% and T d, max values of all polyesters were higher than 360 °C and 390 °C, respectively. Compared with PBN, PBNF25, PBNF50, PBNF75 and PBF exhibited much higher elongation at break (214–295%) and bio-based content (46–100%). Highlights: A series of bio-based copolyesters have been successfully synthesized from FDCA, 2, 6-NDCA and BDO. The effects of composition on thermal properties, mechanical properties and UV blocking properties were investigated. PBN and PBNF25 can crystallize rapidly. However, the crystallization rates of PBNF50, PBNF75 and PBF are very slow. PBNF25, PBNF50 and PBNF75 possessed UV-protectant properties.